THE INFLUENCE OF VIRAL MARKETING ON PURCHASE DECISIONS MODERATED BY CELEBRITY ENDORSERS(A Study on Skintific Consumers in Denpasar City) - Ivana Shaina Putridewi; I Wayan Santika (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The trend of using cosmetic and skincare products in Indonesia has increased since the Covid-19 pandemic, in line with the growing public awareness of self-care. Skintific, as a beauty brand, has leveraged viral marketing and celebrity endorsers to promote its products, particularly among the youth. This study aims to analyze the influence of viral marketing on purchase decisions and examine the role of celebrity endorsers as a moderating variable. The research was conducted on Skintific consumers in Denpasar City, with a total sample of 120 respondents determined using purposive sampling. The data analysis technique used was Moderated Regression Analysis (MRA). The results indicate that viral marketing has a positive and significant effect on purchase decisions. Additionally, celebrity endorsers are proven to moderate the relationship between viral marketing and purchase decisions, where the presence of celebrities strengthens the influence of viral marketing in encouraging consumers to make purchases. These findings contribute to the reinforcement of consumer behavior theory and the Uses and Gratifications Theory in the context of digital marketing for beauty products.